A Review on the Advanced Maintenance Approach for Achieving the Zero-Defect Manufacturing System - Jun, Hong-Bae (Frontiers in Manufacturing Technology, 2022)
Recently, a revolutionary change is taking place in manufacturing and production systems thanks to the development of various advanced technologies such as IIoT (Industrial Internet of Things), CPPS(Cyber-Physical Production System), digital twins, big data analytics, AI (Artificial Intelligence), and so on. One of the change is that